進路発達における自己実現の過程と構造 : メタ認知的考察 - 足立, 明久 (進路指導研究, 1988)
The purpose of this study was to investigate the process and the structure of self-actualization in career development from a viewpoint of metacognition. Two scales were developed to measure; (l)self-actualization (3 items), and(2)the metaconitive process of self-actualization (14 items). These two scales and CDT-3 (Career Development Test) partialy modified were administered to 223 male university students in total. The main results were as follows: (1)The degree of self-actualization was significantly correlated to metacognitive score in the process of self-actualization. (2) In the subjects who's CDT-3 score was higher, metacognitive score was also higher. These findings suggest that metacognition plays an important role in self-actualization related to career development. {3)As the selfactualization scale could be regarded as a kind of metacognitive scale, the two scales were combined and a principal factor method was carried out on the scale scores. After considering the results of 6 subject groups, three major factors were extracted. They consist of each metacognition concerning, (1)value related to ideal self, (2)such motivational elements as expectancy that one's effort will lead to one's intended performance or outcomes, and (3)strategy and procedure. In conclusion, the metacognitive process of self-actualization is assumed to be describe in such a hypothetical formula as "Value×Expectancy×Strategy." Especially, in the systematical instruction of metacognition fostering career development, it seems to be important that "value" should be placed as the fundamental factor.